Functional annotation of hypothetical proteins involved in multiple stress response in Oryza sativa - PRATHEEK H P; SHIVANI NAGAR; SANDEEP ADAVI; VISWANATHAN CHINNUSAMY; RAKESH PANDEY (The Indian Journal of Agricultural Sciences, 2021)
Plants being sessile in nature face multiple stresses during its growth and development. Understanding the dynamic tolerance mechanism of plants to changing environment is the need of the hour and developing climate smart crops is still a nightmare. Functional characterization of relevant genes is a prerequisite when identifying candidates for crop improvement, in this study we identified 66 multiple stress responsive genes in rice that could serve as potential candidates for breeding for stress tolerance. The 15 hypothetical genes rendering multiple stress tolerance were functionally annotated using a rich set of tools ranging from sequence similarity search to fold recognition methods. It is predicted that the query protein might be a copper chaperone for superoxide dismutase. A novel approach to annotate hypothetical proteins with different remote homology search and structure-based threading approaches was designed. In addition to identified multiple stress responsive proteins in rice (Oryza sativa L.), our study also provides a robust toolkit to annotate other hypothetical proteins in plants.